Kemampuan Menulis Teks Eksplanasi Siswa Sekolah Dasar SD Negeri Saruaso - Muhammad Rizki; Chandra Chandra; Inggria Kharisma (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
This study aims to describe the ability of sixth-grade elementary school students in understanding and writing explanatory texts. The method used in this research is a qualitative approach with descriptive techniques. The subjects of the study were five sixth-grade students selected purposively. Data were collected through a 10-item multiple-choice test. The results showed that three students achieved perfect scores (10 correct), one student answered 9 correctly, and another answered 8 correctly. In the writing task, all students were able to compose explanatory texts with appropriate structure. However, weaknesses were found in the linguistic features, particularly in the use of causal conjunctions and scientific terminology. These findings indicate that students have a good grasp of the basic concept of explanatory texts but require further guidance in mastering linguistic elements.